Perbedaan Faktor-Faktor Karakteristik Usahatani Bawang Merah pada Sistem Pengairan Pompa dengan Tadah Hujan di Desa Songan A, Kecamatan Kintamani, Kabupaten Bangli - AGUNG, I DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.1, Januari 2019DO - 10.24843/JAA.2019.v08.i01.p13, 2019)
Differences factors in characteristics of shallot farming in rainfed pump irrigation systems in Songan A Village, Kecamata Kintamani, Bangli Regency, Bali Province Shallot is an agricultural commodity that is needed in small amounts, but everyone loves it and almost every dish requires it. Thus red onion plays an important role in trade and at some point the price can soar. The purpose of this study was to look for differences in the characteristics of shallot farming factors in a rainfed pump irrigation system. Data was collected by a survey method that was taken in a simple random manner on each Banjar that had onion farmers so that the sample size was 100 people in each irrigation group. Using discriminant analysis, the results of the analysis of the characteristics of onion farming factors that have a very significant effect, namely the cultivation of onion farming, seeds, fertilizers, outside family labor, family labor, farmer education, depreciation costs productivity, and income of onion farming. Factors that have only real influence on the age of the farmers, while those that do not affect the number of family dependents and medicines.